Sexual Behaviour among Adolescents in Senior High Schools within the Tamale Metropolis, Northern Region of Ghana - Attibu, R.I.E. (University of Ghana, 2015)
Adolescents’ sexual and reproductive health is a top priority of policy makers around the world. However, risks associated with their sexual behaviour continue to increase. Adolescents engage in sexual intercourse before finishing high school. In the era of HIV/AIDs and other STIs, it is found that either not using condom or having had multiple sexual partners is a significant problem among adolescents. Adolescents are increasingly learning about sexual issues from their peers but not from the family that serves as the first form of socialization and a medium to grooming the child into adulthood. It is in the light of this that the study sets out to examine the sexual behaviour among in-school adolescents within the Tamale Metropolis. Self-administered questionnaires were used to elicit information from four Senior High Schools within the Tamale Metropolis. Simple random sampling technique was used to select a sample size of 424. Data analysis was carried out quantitatively using the computer packages, Statistical Package for Social Sciences. Data collected revealed a worrying sign as 247 (58.3%) of the sample have had sex and 83.3% of those who had sex reported they did not use condom. On the issue of sources of sex information, the data revealed that 94 (22.5%) received education from their family, 136 (32.6%) from their teachers and 121 (29.0%) from their friends. Also, 82.6% of adolescents who received information from friends were found to have had sex. Sex education by parents could not have improved abstinence as 54.0% of respondents asserted that being talked to by parents cannot make them abstain whiles 46% indicated that sex education from parents could make them abstain.Early sexual intercourse continues to increase considerably among adolescents even before they complete Senior High School. They do this irrespective of their religion, parents’ economic status and type of school they attend. In-school adolescents are found to obtain sexual information mainly from their teachers because they believe that their teachers are more knowledgeable. However, regardless of the knowledge acquired, the study indicated that in-school adolescents’ still engaged in an early sex as information from their friends influence their decision to engage in an early sexual intercourse.
Thesis(MPH)-University of Ghana, 2015
Keywords: Sexual Behaviour; Senior High Schools; Tamale Metropolis